Effect of kenaf fibre and rice husk incorporation on melt flow and mechanical properties of calcium carbonate/Polypropylene hybrid composite / Mohd Muizz Fahimi Mohamed and Rahmah Mohamed - Mohd Muizz Fahimi, Mohamed; Rahmah, Mohamed (2015)
This research is conducted to determine the changes in melt flow and mechanical properties of kenaf and rice husk mix on hybrid composite filled with calcium carbonate, CaCo3/PP hybrid matrix. Variable ratios of hybrid composite were incorporated using kenaf fibre (KF) and rice husk (RH) particulates which were mixed in different composition of 10:30, 15:25, 20:20, 25:15, 30:10, 35:5 with fixed 20% amount of CaCO3. Compounded hybrid composite was prepared via twin screw compounder and tested for melt flow index (MFI), tensile and impact strength. When added with kenaf and rice husk, the composites exhibited lower MFI. All compounds showed MFI range from 2 to 3 gram/10 min. Highest MFI was observed with the highest ratio of rice husk to kenaf fibre (KF/RH 10:30) whilst the lowest MFI value was exhibited by the composite ratio of KF/RH 35:5 incorporated into the mix of CaCo3/PP hybrid matrix. This implied that incorporation of kenaf fiber has resulted in higher resistance of the hybrid matrix thus causing the melting flow index to increase accordingly. Tensile strength, elongation at break and impact properties of hybrid composite have decreased due to the increasing content of the rice husk. For tensile properties, better stress transfers were exhibited by higher RH compared to KF which are shown from their higher tensile strength. Molecular interactions of CaCo3/PP hybrid matrix can efficiently be provided by the stress transfer of RH after the addition of the filler into the hybrid. Meanwhile Young Modulus, E was also increased with addition of higher KF in CaCo3/PP hybrid composite mainly due to greater rigidity imposed by the fibrous kenaf. Impact strength was improved with higher rice husk content KF/RH 10:30. The higher toughness of higher rice husk content for hybrid composite showed that rice husk provide better resistant to fracture embrittlement. The rice husk enhances the impact forces subjected to the hybrid composite due to high silica content in rice husk and its particulates.